UTILIZATION OF Penaus monodon SHRIMP SHELL WASTE AS ADSORBENT OF CADMIUM(II) IN WATER MEDIUM - Sari Edi Cahyaningrum; Amaria Amaria (Indonesian Journal of Chemistry, 2005)
Utilization of shrimp shell has been optimum so that in this research preparation of adsorbent chitosan from shell of shrimp (Penaus monodon) as raw materials for cadmium(II) adsorption was carried out. The chitin was made by the deproteination, demineralization; chitosan was prepared by chitin deacetylation. This work was started with Infra Red Spectroscopic identification of functional group. Percentage of deacetylation was determined also by Infra Red Spectroscopy. Contant of nitrogen was determined by Kjeldhal method. The isotherm adsorption Langmuir model was employed for the determination of the energy and the capacity in adsorption. Result showed that chitosan could be isolated from shrimp shell waste with % deacetylation degree of 79.80 and % nitrogen 7.11. Cadmium(II) was chemically adsorbed on chitosan involving energi adsorption of 32.27 kJ/mole. Adsorption capacity of cadmium(II) was 6.35 x 10-5 mole/g. The constant adsorption rate k, was 0.91 x 10-3 s-1 and equilibrium adsorption desorption are K = 10.28 x 103. The ability adsorption of chitosan in real waste has the efficiency of 90%.